Indications of Selenium Protection against Cadmium and Lead Toxicity in Oilseed Rape (Brassica napus L.) - Wu, Zhilin; Yin, Xuebin; Bañuelos, Gary S.; Lin, Zhi-Qing; Liu, Ying; Li, Miao; Yuan, Linxi (Frontiers in Plant Science, 2016)
The present study investigated the beneficial role of selenium (Se) in protecting oilseed rape (Brassica napus L.) plants from cadmium (Cd+2) and lead (Pb+2) toxicity. Exogenous Se markedly reduced Cd and Pb concentration in both roots and shoots. Supplementation of the medium with Se (5, 10 and 15 mg kg-1) alleviated the negative effect of Cd and Pb on growth and led to a decrease in oxidative damages caused by Cd and Pb. Furthermore, Se enhanced superoxide free radicals (O2-), hydrogen peroxide (H2O2) and lipid peroxidation, as indicated by malondialdehyde (MDA) accumulation, but decreased superoxide dismutase (SOD) and glutathione peroxidase (GPx) activities. Meanwhile, the presence of Cd and Pb in the medium affected Se speciation in shoots. The results suggest that Se could alleviate Cd and Pb toxicity by preventing oxidative stress in oilseed rape plant.